Determination of pedestrian displacement velocity for ground exploration programs (2017)
In Engineering and Geophysics field exploration, uncertainty for determination of the velocity of ground data acquisition due to extreme topographic conditions has been underestimated in the calculation of the displacement time between stations or sampling points. This lack of reliable models, negatively affects the determination of costs and planning of fieldwork activities. Known models of times and routes of displacement determination such as the “Smaller Cost Routes” are based on the effect of the type of land and the slope. However, these models consider the effect of the slope by means of subjective impedance values which has no a clear physical meaning. Furthermore, the upslope or downslope displacement is not considered to affect the reliability of velocity estimation. In this paper, a model of displacement velocity is proposed taking into account the upslope/downslope factor. The model was determined using real data from a topographical survey along a pipeline of 880 Km extended along terrains with changing climatic and topographic conditions. As a result, the proposed model improves the selection of optimal routes for a reliable time and cost estimation.